Chalk Back: The Girl and Youth-Led Street Art Movement to #StopStreetHarassment. Issue 2 (1st June 2020) - Harris-Harb, Natasha; Sandberg, Sophie
Abstract : The Chalk Back movement that started in March 2016 is a rapidly growing collective of over 150 young activists from around the world. As part of a university class project, Sophie decided to collect experiences of street harassment, write them out verbatim with chalk on the streets where they occurred alongside the hashtag #stopstreetharassment, and post them on the Instagram account @catcallsofnyc. Two years later, the account gained popularity. Other catcallsof accounts opened in London, Amsterdam, Ottawa, Dhaka, Nairobi, Cairo, and Sydney. These accounts, discussed below, are just a few of those spanning 150 cities in 49 countries in 6 continents. We are two Chalk Back members—Natasha from Ottawa and Sophie from New York City—highlighting the risk, empowerment, and power dynamics of what we call chalking back by amplifying the voices of those doing this work around the world.